Medical cannabis in the treatment of cancer pain and spastic conditions and options of drug delivery in clinical practice - Landa, Leos; Jurica, Jan; Sliva, Jiri; Pechackova, Monika; Demlova, Regina (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2018)
The use of cannabis for medical purposes has been recently legalised in many countries including the Czech Republic. As a result, there is increased interest on the part of physicians and patients in many aspects of its application. This mini review briefly covers the main active substances of the cannabis plant and mechanisms of action. It focuses on two conditions, cancer pain and spasticity in multiple sclerosis, where its effects are well-documented. A comprehensive overview of a few cannabis-based products and the basic pharmacokinetics of marijuana's constituents follows. The review concludes with an outline for preparing cannabis (dried inflorescence) containing drug dosage forms that can be produced in a hospital pharmacy.
Keywords: nádorová bolest; cancer; Muscle Spasticity; způsoby aplikace léků; marihuana pro léčebné účely; Phytotherapy; Plant Preparations; Cancer Pain; Analgesics, Opioid; rostlinné přípravky; opioidní analgetika; Cannabinoids; spasms; cannabis; mechanism of action; pain; kanabinoidy; cannabinoids; fytoterapie; Humans; Medical Marijuana; THC; svalová spasticita; lidé; multiple sclerosis; Drug Administration Routes